Antimicrobial susceptibility and molecular characteristics of Mycoplasma pneumoniae isolates from children in Xi'an regions of China - Huang, Chao; Yang, Jun; Cao, Jia; Ren, Haiyan; Gao, Nan; Liu, Jianjun (Frontiers in Pediatrics, 2025)
IntroductionMycoplasma pneumoniae (MP) is a primary cause of pediatric pneumonia, with rising macrolide resistance being a global concern. Data on its molecular epidemiology and resistance patterns in Xi'an, China, are limited. This study aimed to characterize MP isolates from children in Xi'an to inform local treatment strategies.MethodsIn 2023, throat swabs were collected from 376 children hospitalized with MP infection. From these, 70 MP isolates were cultured. Antimicrobial susceptibility testing was performed, and isolates were genotyped using PCR-MALDI-TOF MS to identify P1 types and mutations in the 23S rRNA gene associated with macrolide resistance.ResultsThe MP culture-positive rate was 18.61% (70/376), with the highest prevalence in school-aged children (5–14 years, 81%). The P1-I genotype was predominant (97%). All 70 isolates harbored A2063G, A2064T, and A2617C mutations in the 23S rRNA gene. However, phenotypic resistance was 38.6% for macrolides, 31.4% for quinolones, and 38.6% for tetracyclines, indicating a significant genotype-phenotype discordance for macrolides.ConclusionMP strains in Xi'an show high rates of genotypic macrolide resistance and a predominance of the P1-I genotype. The notable discordance between the universal presence of resistance mutations and observed phenotypic resistance underscores the importance of integrating both molecular and culture-based susceptibility testing to guide effective clinical management.